Reality and perspectives of the profession surgical in Uruguay - Bogliaccini, Gustavo; Piacenza, Gustavo; Bastarrica, Ernesto; Meerhoff, Ricardo (Cirugía del Uruguay, 1990)
We are grateful, as is the style, to the Authorities of the XXXIX Uruguayan Congress of Surgery that we have entrusted the coordination of this Table. As you know there are two kinds of men, those who look at the events that happen and they wonder the why of them and a second category, among which I have always dealt to find me, those who dream dreams and they wonder why not? We have chosen to try to show reality stark and point out their socioeconomic foundations, trying to highlight their causal relationship- effect.